Pengaruh Marketing Public Relations Cloud cakes Terhadap Peningkatan Citra Positif - Najwa Shahab; Karimah Faizah; Nasywa Rahmadhita; Sadiyah El Adawiyah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Cloud Cakes is a food brand, or can be said to be a cake dessert that in August 2025 was discussed by the public on social media because many influencers reviewed Cloud Cakes. This study aims to analyze the influence of public relations marketing implemented by Cloud Cakes on improving Cloud Cakes positive image, as well as to measure data whether Cloud Cakes implements public relations marketing and whether it has an effect on improving Cloud Cakes positive image. This study uses a quantitative method approach. The number of samples in this study was 43 respondents. The sample research used a probability sampling technique, meaning that each population was given the opportunity to be selected as a sample. The data collection technique in this study was by distributing 11 statements through a questionnaire announced via Google Form. From the results of the data analysis, it can be seen that the t-test value is 0.000, which indicates that there is an influence of Cloud Cakes public relations marketing on improving the positive image. This study concludes that there is an influence of public relations marketing on improving the positive image based on the data that has been explained through SPSS.